Optimal design of forest and capital income taxation in an economy with an Austrian sector - Koskela, Erkki, 1946-2020.; Ollikainen, Markku, 1952- (Helsinki : Research Institute of the Finnish Economy, 1997)
Tiivistelmä.
Keywords: metsäverotus; pääomatulot; verotus; pääomaverotus